Računalniška analiza ogrevalnih in hladilnih obremenitev za različne tipe stavb - Stritih, Uroš (Strojniški vestnik, 2000)
This paper presents simulations of heating and cooling loads for different types of building with the TRNSYS programme package. We present seven different building types and four different weather conditions in the European Union. Altogether we made 28 simulations and the results for an office building are shown in this paper.
Keywords: zgradbe pisarniške; energija toplotna; simuliranje obremenitev; analize računalniške; bivalno okolje; klimatizacija; simulacija; računalniška analiza